Incidence of carbon pricing in Tanzania: Using revenues to empower low-income households with renewable energy - Abigail O. Asare; Laura Schürer (University of Oldenburg, Department of Economics, 2024)
While Tanzania's greenhouse gas emission levels still seem low by international comparison, the country is rapidly carbonizing, and most households still rely on kerosene, charcoal, and firewood for cooking and lighting. Carbon pricing can be an effective tool to discourage the creation of high carbon lock-ins, to generate substantial revenues, and to channel them toward sustainable development. Employing a microsimulation approach that integrates multiregional input-output and household-level data, we examine the distributional impacts of four different carbon pricing designs and five compensation schemes on Tanzanian households. We find that national carbon pricing would have progressive effects but with large horizontal differences. Revenue-financed cash or infrastructure transfers would effectively mitigate adverse impacts on low- and middle-income households. We suggest the use of carbon pricing revenues to provide low-income households with access to renewable energy appliances such as solar lights and solar cookers to empower them through long-term cost and time savings as well as health benefits. This would contribute not only to alleviating poverty but also to achieving Tanzania's electrification and clean cooking objectives.
Keywords: D57; H23 Q52; Q54; O55; 330; Climate policy; Carbon pricing; Tax incidence; Distributional effect; Inequality; Sustainable development; Renewable energy; Sub-Saharan Africa; Tanzania